Architectural issues - Zelkowitz, Marvin V., 1945- (Amsterdam ; Boston : Elsevier Academic Press, 2004)
The series covers new developments in computer technology. Most chapters present an overview of a current subfield within computer science, with many citations, and often include new developments in the field by the authors of the individual chapters. Topics include hardware, software, theoretical underpinnings of computing, and novel applications of computers. This current volume emphasizes architectural issues in the design of new hardware and software system. An architectural design evaluation process is described that allows developers to make sure that their source programs adhere to the architectural design of the specifications. This greatly aids in the maintenance of the system. Telecommunications issues are covered from the impact of new technology to security of wireless systems. Quantum computing, an exciting development that may greatly increase the speed of present computers, is described. The book series is a valuable addition to university courses that emphasize the topics under discussion in that particular volume as well as belonging on the bookshelf of industrial practitioners who need to implement many of the technologies that are described. In-depth surveys and tutorials on new computer technology Well-known authors and researchers in the field Extensive bibliographies with most chapters All chapters discuss aspects of architectural design of new hardware and software Quantum computing is an exciting new prospect for future machine design.
Preface -- Contributors -- 1. Evaluating software architectures ---- Roseanne Tesoriero Tvedt, Patricia Costa, and Mikael Lindvall -- 2. Efficient architectural design of high performance microprocessors ---- Lieven Eeckhout and Koen De Bosschere -- 3. Security issues and solutions in distributed heterogeneous mobile data systems ---- A.R. Hurson, J. Ploskonka, Y. Jiao and H. Haridas -- 4. Disruptive technologies and their affect on global telecommunications ---- Stan McClellan, Stephen Low, and Wai-Tian Tan -- 5. Ions, atoms, and bits: An architectural approach to quantum computing ---- Dean Copsey, Mark Oskin, and Frederick T. Chong.
Includes bibliographical references and index.
Keywords: Computer architecture; Software architecture; Computer engineering; Electronic books